DETERMINATION OF RATIONAL PARAMETERS OF SUPPORTING STRUCTURES MADE OF SOIL-CEMENT PILES ON LANDSLIDE-PRONE SLOPES - Tiutkin, O. L.; Ihnatenko, D. Y. (Science and Transport Progress, 2021)
Purpose. The article proposes a method for determining the rational parameters of supporting structures made of soil-cement piles on landslide-prone slopes. Methodology. To achieve this purpose, the authors performed comparative calculations of finite-element models of landslide-prone layered slope with the arrangement of supporting structures of soil-cement piles: vertical, located at an angle to the vertical axis, combined with a concrete grillage, without grillage, with different diameters, with different distances between piles, but of the same length, which is justified by the location determined by preliminary calculations of the sliding surface. Findings. According to the results of calculating the contact problem of the interaction of the soil mass and the supporting structure, the regularities of formation of strength and stability of the reinforced landslide-prone slope were obtained, which makes it possible to predict its geomechanical stability depending on the possible location of the sliding surface curve. The method of increasing the stability coefficient of the soil slope depending on the variation of the parameters of the soil-cement supporting pile structure is substantiated. Numerical calculations substantiate the parameters of soil-cement pile supporting structures – the length of the piles, their diameter, the distance between the piles, the angle of their inclination and the feasibility of combining the piles with a concrete grillage. Originality. For the first time, the formation regularities of strength and stability of soil-cement supporting structure for strengthening the landslide-prone slopes are obtained, which makes it possible to predict their geomechanical stability depending on the possible location of the sliding surface curve. For the first time, the dependences of changes in absolute displacements, relative deformations, coefficients of strength, stability, as well as Mises stresses in the elements of supporting structures of soil-cement piles on the angle of their inclination, distance between piles and the presence of a concrete grillage that joins them. Methods for assessing and predicting the landslide danger of soil slopes were further developed, which allowed to substantiate the method of increasing the strength coefficient depending on the variation of the parameters of the soil-cement supporting structure. For the first time, the parameters of the method of increasing the stability of landslide-prone slopes with pile supporting structures based on the complex mathematical and centrifugal modeling using real landslides and similarity criteria are substantiated. Practical value. The authors have developed and patented a method of strengthening landslide slopes with the help of soil-cement piles, combined with a concrete grillage, located perpendicular to the movement vector of the landslide body.